2018
DOI: 10.1007/s11562-018-0415-0
|View full text |Cite
|
Sign up to set email alerts
|

Reaching out in a climate of negativity: perceptions and persistence among Muslim sources engaging with news media

Abstract: The conceptions sources have of journalists influence whether and in what ways those sources engage with the news media. In this paper, I consider the contribution of Muslim sources to news in a context of perceived negativity. Scholarship on the content of British news stories about Muslims has found a consistently negative tone; my study examines the impressions of sources as co-producers of that content. My data come from qualitative fieldwork conducted in Glasgow, Scotland, studying relationships between j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Also, the exaggerated negative reactions of society against the Muslims and the Druze could be attributed to the role of media. Inaccurate reports spread negative perceptions about these two communities [74]. A similar study in India has shown that the entire Muslim community was stigmatized as the spreader of the virus, using expressions such as "Corona terrorism, " "enemies of humanity" and "Corona Jihad" [75].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the exaggerated negative reactions of society against the Muslims and the Druze could be attributed to the role of media. Inaccurate reports spread negative perceptions about these two communities [74]. A similar study in India has shown that the entire Muslim community was stigmatized as the spreader of the virus, using expressions such as "Corona terrorism, " "enemies of humanity" and "Corona Jihad" [75].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of Muslim sources to news is in a context of perceived negatively. The news stories about Muslim has found a consistently negative tone (Munnik, 2018). Islamophobia is also racism and discrimination against Muslims affecting the prosperity for young adult Muslims to identify as both Muslim and American (Hummel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social research identifies dissatisfaction among British Muslims with media narratives (Samad 1998;Kabir 2010;Ali and Hopkins 2012;Al-Azami 2016). Even among sources who speak with journalists and contribute to news coverage, the primary word characterising that coverage is "negativity" (Munnik 2018). Muslim organisations in the UK are now countering this narrative: Muslim Engagement and Development (MEND) provide resources to equip individual Muslims or community groups to monitor and respond to media coverage (Muslim Engagement and Development n.d.); an informal monitoring campaign on social media has evolved into the Centre for Media Monitoring (Subramanian 2018;Muslim Council of Britain 2018).…”
Section: Introductionmentioning
confidence: 99%